IN VITRO ANTIMICROBIAL ACTIVITY OF PUNICA GRANATUM L. EXTRACT AND ANTI-INFLAMMATORY ACTIVITY OF NANO GEL IN VIVO INWISTAR RATS GINGIVA - SYAHPUTRA, ARMIA; ERVINA, IRMA; DARWIS, AIDA FADHILLA; SYAHPUTRA, HAFID; MARPAUNG, EMI SARAH NOVITA; SITORUS, INDAH JAYANTI; ADITYA, REZA (International Journal of Applied Pharmaceutics, 2025)
Objective: This study evaluates the antimicrobial activity of pomegranate (Punica granatum L.) peel extract in vitro and the anti-inflammatory effects of its nano gel formulation in vivo on gingival inflammation in male wistar rats. Methods: The antimicrobial activity was tested against Aggregatibacteractinomycetemcomitans, Porphyromonasgingivalis, and Fusobacterium nucleatum using ethanol, ethyl acetate, and n-hexane extracts at concentrations of 0.8–25%. The anti-inflammatory effect was assessed using pomegranate peel extract nano gel (6.25%, 12.5%, and 25%) in a ligature-induced gingivitis model in Wistar rats, with Gengigel as a positive control. Evaluation parameters included inhibition zone diameters for antimicrobial activity, while histological analysis of lymphocyte, neutrophil, and macrophage counts was conducted on days 3 and 7 to assess anti-inflammatory effects. Results: The 25% ethanol extract exhibited the highest antimicrobial inhibition zones (16.95 mm for A. actinomycetemcomitans, 16.83 mm for P. gingivalis, and 16.35 mm for F. nucleatum, p<0.05). The 25% nano gel formulation significantly reduced inflammatory cell counts compared to the control (p<0.05), showing reductions in lymphocytes (4.33±1.53), neutrophils (1.00±0.00), and macrophages (1.67±0.57) by day 7. Conclusion: Pomegranate peel extract demonstrated potent antimicrobial properties, especially in ethanol-based formulations. The nano gel formulation exhibited significant anti-inflammatory effects, with the 25% concentration proving the most effective in reducing gingival inflammation. These findings highlight its potential as a natural therapeutic agent for periodontal disease management.